Application of ESP32-CAM for Cloud-Based Surveillance System in 3D Printing Machine - Ilham Saputra; Khoirul Ashabi (Politeknik Negeri Bengkalis, 2022)
The working monitoring process at this time requires accuracy and foresight to maximize the work results. One of them is the process of manufacturing on a 3d Printing machine that requires monitoring, where the printing process is very susceptible to failure caused by several factors when the machine is processing. Therefore, innovations are needed to anticipate work activities by utilizing the Internet of Things (IoT) feature to perform the monitoring process anywhere and anytime. We propose the new development system using ESP32-CAM microcontroller to be used in this study by utilizing the wireless features found on the board. The working process can be adequately monitored by connecting the IP address tunnel from the local port to the ngrok Server. The design and manufacture of this tool use ESP32-CAM which has been applied to a programming language that is uploaded using the Arduino IDE. The final result of this research is the manufacturing process on 3D printing machines can be monitored in real-time and cloud-based. The monitoring process will display an image connected to the local port using tunneling from the ngrok Server.